Pengembangan Pewarna Rambut dari Ekstrak Kental Gambir (Uncaria gambir Roxb.) dalam Sediaan Setengah Padat - LATIRAH LATIRAH; TETI INDRAWATI; ANNY VICTOR PURBA (Fakultas Farmasi Universitas Pancasila, 2015)
Gambier (Uncaria gambir Roxb.) is one of the alternatives used as a natural colouring agent in foods and drinks. The aim of this research was to develop extract gambier as a hair dye. Gambier extract was obtained by macerated with water in base condition (pH 8-10). The resulting extract was evaluated for hair adhesion, organoleptic, physical, chemical and irritation test to rabbit’s skin. Viscous gambier extract has 0HUE value of 338.73 ± 0.116 (purple), can be processed into permanent hair colour cream with 0HUE value of 42.167 ± 0.231 (red), pH 8, ammoniac odor, produce red yellowish hair with 0HUE value of 53.43 ± 0.060, fulfil requitment for microbiology, not iritant to rabbit's skin has density of 0.903 0.006 g/L and viscosity of 13,100 ± 0.000 cP.